2021
DOI: 10.1111/jac.12502
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal for organic amendments and plant growth‐promoting rhizobacteria to enhance crop productivity under drought stress: A review

Abstract: Plants are sessile organisms, frequently face unfavourable growth conditions such as drought, salinity, chilling, freezing and high‐temperature stresses, inhibiting growth and development, and ultimately reducing crop productivity. Among these stresses, drought stress has been a major challenge for sustainable crop production and a hot area of research under the current climate change scenario. Organic amendments such as biochar (BC) and compost along with plant growth‐promoting rhizobacteria (PGPR) could be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 101 publications
(175 reference statements)
1
51
0
Order By: Relevance
“…PGPR are eco-friendly efficient biotechnological tools to improve plant water uptake and growth in various, especially stressful, conditions [18]. PGPR application is a sustainable strategy for increasing crop production under drought stress and replacing chemical fertilizers [29]. In the present study, the yield components of the Azar-2 rainfed cultivar, including biological yield, grain yield, straw yield, and 1000-seed weight, were significantly affected by the applied F, B, N1, and N2 PGPR as seed-inoculated plants showed higher means than noninoculated controls.…”
Section: Discussionmentioning
confidence: 99%
“…PGPR are eco-friendly efficient biotechnological tools to improve plant water uptake and growth in various, especially stressful, conditions [18]. PGPR application is a sustainable strategy for increasing crop production under drought stress and replacing chemical fertilizers [29]. In the present study, the yield components of the Azar-2 rainfed cultivar, including biological yield, grain yield, straw yield, and 1000-seed weight, were significantly affected by the applied F, B, N1, and N2 PGPR as seed-inoculated plants showed higher means than noninoculated controls.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study are in agreement with the findings obtained by Ahmad et al [52], who reported that co-inoculation of Rhizobia and PGPR can enhance root length and cause an increase in the uptake of water from deeper soil regions. Ullah et al [53], Mumtaz et al [54] and Fatawi et al [55] argued that the use of rhizobacteria and organic amendments (compost and biochar) increases the root surface area, root length and stomatal conductance, that, in turn, improve the absorption of water from deeper regions and ultimately result in an increase in RWC. Co-inoculation of PGPR and Rhizobium possessing ACC-deaminase activity promotes roots elongation that aids the plant to absorb more water from soil [49].…”
Section: Discussionmentioning
confidence: 99%
“…Healthy soil is essential for plant growth in the natural environment. In the recent past, various environmental and ecological issues such as soil contamination, soil degradation, fertility loss with a decline in crop yield, water shortages, and climatic change have led to an increased trend in biotic and abiotic stresses that ultimately pose a threat to food security (Gregory et al 2014;Ren et al 2016;Albert et al 2021;Saffeullah et al 2021;Ullah et al 2021). Soil contamination through inorganic and organic contaminants is a well-known problem; therefore environmentally safe and economically viable remediation techniques are urgently needed (Ren et al 2016;Mehmood et al 2019).…”
Section: Introductionmentioning
confidence: 99%